Planta de capacitación y procesamiento tecnificado agroindustrial “acodo de Gachancipa” (2021)
Project located in the Municipality of Gachancipá, which is within the Bogotá - Tunja corridor, which has a problem in the environmental impact, due in large part to the pollution generated in the Bogotá river, deforestation and mining exploitation, therefore, generates the Lung of Environmental Reactivation, this due to the central strategic location of the municipality, at the national corridor level, and its important geographical limits, such as the Tominé Reservoir, the Bogotá river, and the La Cabrera hill. Where the main objective is the environmental recovery of the corridor supported by a series of projects to support the intervention of the Central Sabana region and the Cundiboyacense Altiplano, managing a methodology in phases from the macro to the micro and punctual and thus, to provide a whole development for the sector in a regional and national way, which is established as a Agroindustrial Technified Plant with management of new productive technologies.